Case Studies on Big Brands Using Influencers to Win Back Lost Customers - Setiawan, Indra (Celebes Scholar pg, 2023)
This research seeks to find the suitability of influencer marketing in the targeting of repeat customer acquisition for the big brands including Coca Cola, Nike and Starbucks. With former customers in the sample, the study employs the methods of using independent samples t-tests, regression analysis, correlation analysis, analysis of variance, and analysis of covariance. The study also shows that when the customers are reengaged through the influencer campaigns, they show statistically significant higher engagement and purchase intention score than the customers who were not reengaged. Credibility of the influencer and the quality of their post proved to have a host influence on re-engagement and intents to make a purchase. In addition, cross comparison of the different brands brought out the differences in success rates of the influencer campaigns. To the best of the author’s knowledge, this study does not aim at the acquisition of new clients but rather the reengagement hence offers rich insights of how influencer marketing can be used strategically to address this issue. Hence, the study emphasises that to support be again strategies and build the ‘doctrinaire of brand endorsement’ it is crucial to identify genuine influencers and produce quality content relevant to the target society.